Editorial (Res Medica, 2013)
After 220 years of journalistic infertility, the Royal Medical Society has given birth to Res Medica and it is appropriate enough that nearly nine months have elapsed since the end of last Session when the idea was first conceived. Previous attempts to publish the Transactions of the Society have on the whole been abortive, and the idea of a regularly produced Journal never seems to have been seriously entertained.